Development of the interval endurance capacity in elite and sub-elite youth field hockey players - Elferink-Gemser, M. T.; Visscher, C.; van Duijn, M. A. J.; Lemmink, K. A. P. M. (British Journal of Sports Medicine, 2006)
Objectives: To gain more insight into the mechanisms that underlie the development of interval endurance capacity in talented youth field hockey players in the 12-19 age band.